Diskursus Perkembangan Ilmu Syarah Hadith: Sebuah Kajian Metodologis dan Historis - Ahmad Nabil Amir (Jurnal Pemikiran Islam, 2021)
The study of the history of the development of hadith and ulumul hadith is one of the studies developed  in Islamic science. This study is important because hadith is the second reference to Islam after the Qur'an. Therefore we need an in-depth study of the discourse on the development of "syarah" hadith. The purpose of this paper is to discuss the development of the science of hadith commentary since the early century of Hijrah. It traces its historical development and contribution in expanding the profound understanding of hadith and its science. This paper attempts to illustrate the discipline of usul al-sharh and set forth its underlying method as presented by hadith scholars in their major works of hadith commentary. The discussion focuses on the method and ittijahat al-sharh in interpreting and commenting rigorously on authentic works of hadith.AbstrakPengkajian tentang sejarah perkembangan hadith dan ulumul hadith merupakan salah satu kajian dalam ilmu keislaman. Hal ini disebabkan karena hadith merupakan rujukan Islam yang kedua setelah al-Qur’an. Oleh karena itu diperlukan sebuah kajian yang mendalam tentang diskursus perkembangan ilmu syarah hadith. Adapun tujuan artikel ini mengkaji dinamika perkembangan ilmu syarah sejak  abad pertama Hijrah. Di dalamnya akan mengelaborasi pertumbuhan dan sumbangannya dalam mengembangkan pemikiran dan pemahama hadith dan ulumul hadith. Selebihnya juga menjelaskan pemahaman usul al-sharh dan menguraikan kekuatan metode yang digunakan oleh ulama dalam menghasilkan kitab-kitab syarah. Perbincangannya menfokuskan kepada manhaj dan ittijahat al-sharh yang digunakan dalam mengupas dan membahaskan kitab-kitab hadith yang muktabar.